A comparative study based on serum SERS spectra in and on the coffee ring for high precision breast cancer detection. (28th May 2022) - Lin, Xueliang; Jia, Xianggang; Lin, Jin Yong; Wu, Ping Hui; Weng, Youliang; Feng, Shangyuan
Abstract: Human blood contains a variety of biomolecules that are highly related to the occurrence, progression, and prognosis of diseases, including cancer. The development of rapid and accurate methods for the detection of these biomarkers with extremely low concentration is vital for improving cancer screening. Herein, a label‐free surface‐enhanced Raman scattering (SERS) technology was employed to detect human serum samples from healthy volunteers ( n  = 51) and breast cancer patients ( n  = 58) with the aim of exploring the differences in bio‐components between them. Moreover, the influence of measurement location during SERS assay was evaluated due to the occurrence of "coffee‐ring (CR)" effect associated with this work. Results showed that the SERS spectra obtained from the CR area can better reflect the overall biochemical information of serum samples and exhibited excellent diagnostic sensitivity (94.8%) and specificity (98%) for identifying breast cancer from healthy groups using principal component analysis and linear discriminant analysis (PCA‐LDA) algorithm. This work showed a preliminary study of the serum SERS method for breast cancer detection, providing a potential rapid and accurate liquid biopsy strategy for clinical cancer screening. Abstract : The combination of SERS technology based on "coffee‐ring" effect and PCA‐LDA algorithm was employed as a rapid, accurate, and label‐free method to identify breast cancer and healthy human serum samples.